A novel bimodal approach for treating atrophic bone non-unions with extracorporeal shockwaves and autologous mesenchymal stem cell transplant. (February 2018) - Sansone, Valerio; Brañes, Manuel; Romeo, Pietro
Abstract: We propose a novel approach for the treatment of atrophic bone non-unions via parallel applications of extracorporeal shock wave therapy (ESWT) and an autologous mesenchymal stem cell transplant. The hypothesis resides on the potentiality of shock waves (SWs) to act as a tool for manipulating the patient's mesenchymal stem cells (MSCs). In addition to the conventional physical stimulus achieved by delivering SWs at the site of non-union to stimulate the well-known trophic effects on bone tissue, a series of concomitant ESWT would be administered in tandem at a bone marrow donor site, such as the iliac crest, to precondition resident bone marrow stromal cells (BMSCs) in vivo, priming resident MSCs by enlarging and conditioning their population prior to bone marrow aspiration. The resulting sample could then be treated to further augment cell concentration and injected, under fluoroscopic control, into the non-union site through a percutaneous approach.